Lithium cobalt oxide positive electrode material as well as preparation method and application thereof
By forming a boron-containing compound coating on the main material of the LiCoO2 positive electrode material, the problem of LiCoO2 capacity attenuation and poor cycle stability at high voltage is solved, and higher capacity and cycle stability are achieved.
Patent Information
- Application Number
- CN202411629025.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing LiCoO2 positive electrode materials have poor capacity attenuation and cycle stability at high voltages, making it difficult to meet the needs of improving energy density and cycle performance.
The main material LixNayCo1-zMzO2 is used to form a boron-containing compound coating on its surface, and a lithium cobalt oxide positive electrode material is prepared by combining high-temperature solid phase sintering and low-temperature solid phase sintering.
The capacity and cyclic stability of the lithium cobalt oxide positive electrode material are significantly improved at high voltages, and show higher first effect, capacity and cyclic stability than conventional O3 phase lithium cobalt oxide.
Smart Images

Figure CN119480994A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium cobalt oxide positive electrode material, a preparation method and application thereof. Background Art
[0002] LiCoO2, a lithium-containing layered transition metal oxide cathode material, was first reported by John B. Goodenough et al. in 1980. The layered structure of LiCoO2 is Li + It provides a 2D diffusion channel and has the advantages of large specific capacity, high voltage, and good cycle performance, and has been widely studied and applied. The space group of conventional LiCoO2 is R-3m, Li + and Co 3+ Layers are arranged alternately in a cubic close-packed O 2- In the octahedral positions formed, LiO6 and CoO6 octahedra are stacked with shared edges, and the arrangement order of the O layer is ABCABC, which belongs to the O3 phase.
[0003] The theoretical capacity of O3 phase LiCoO2 is as high as 274mAh / g, which has a very high volumetric energy density, but the actual capacity release of LiCoO2 is closely related to the charging voltage. In order to further improve the capacity performance and energy density of LiCoO2, it is necessary to continuously increase the charging voltage of LiCoO2. Therefore, researchers have conducted extensive research on high-voltage LiCoO2. With various theoretical studies, coating and doping modifications, the voltage of LiCoO2 has been gradually increased, but when charged to 4.5V and above, the capacity attenuation mechanism of LiCoO2 in organic electrolyte is more complicated, which is not only related to the crystal structure and electronic structure of the material itself, but also to the type of electrolyte and the properties of the interface. At the O3-H1-3-O1 phase transition that begins at 4.5V, the reversibility of the slip phase transition of the CoO2 plate layer is reduced, and the particles undergo a c-axis contraction of more than 3%. At the same time, due to the Co 3+ / 4+ :3d energy band and O 2- : The top of the 2p band overlaps, resulting in the O 2- It will provide charge compensation and cause oxidation reaction, and O2 will be released from the lattice, causing damage to the material. In addition, some researchers have found that when charged to a higher potential, the interface of LiCoO2 is unstable and a spinel phase with low electrochemical activity will be generated. In addition, some researchers believe that certain solvents in the organic electrolyte will react with the surface of LiCoO2, causing the LiCoO2 interface to change or even dissolve.
[0004] At present, there is an urgent need to develop lithium cobalt oxide positive electrode materials with higher capacity and better cycle stability under high voltage compared with conventional O3 phase lithium cobalt oxide.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a lithium cobalt oxide positive electrode material, a preparation method and application thereof, which has higher capacity and better cycle stability under high voltage.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a lithium cobalt oxide positive electrode material, comprising a main material and a boron-containing compound coating layer coated on the main material;
[0009] Among them, the general formula of the main material is Li x Na y Co 1-z M z O2, M is at least one selected from Mg, Al, W, Ti, La, Zr, Y, Ni and Mn, 0.9≤x≤1, 0≤y≤0.1, 0<z≤0.1, and 0.9<x / (1-z)<1;
[0010] The main XRD peak of lithium cobalt oxide positive electrode material is located at 18.6±0.1°.
[0011] In an optional embodiment, in the lithium cobalt oxide positive electrode material, the mass fraction of the boron-containing compound is 0.1%-1.0%.
[0012] In a second aspect, the present invention provides a method for preparing the lithium cobalt oxide positive electrode material of the aforementioned embodiment, comprising: mixing and sintering a sodium source and a cobalt source to obtain a P2 phase precursor;
[0013] The P2 phase precursor and the lithium source are mixed and then subjected to molten salt ion exchange treatment to obtain a T2&O2 composite lithium cobalt oxide material;
[0014] The T2&O2 composite lithium cobalt oxide material is treated with lithium in a lithium salt solution to obtain O2 phase lithium cobalt oxide;
[0015] A boron compound coating layer is formed on the O2 phase lithium cobalt oxide.
[0016] In an optional embodiment, the preparation process of the P2 phase precursor includes: mixing a sodium source, a cobalt source and an M source, and performing high temperature solid phase sintering at 700° C. to 900° C. for 8 h to 30 h; M is selected from at least one of Mg, Al, W, Ti, La, Zr, Y, Ni and Mn;
[0017] Optionally, the molar ratio of sodium to cobalt is controlled to be (0.6-1.0):1;
[0018] Optionally, the cobalt source is selected from at least one of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide;
[0019] Optionally, the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate;
[0020] Optionally, during the high-temperature solid-phase sintering process, the heating rate is controlled to be 1°C / min-10°C / min.
[0021] In an optional embodiment, during the preparation of the T2&O2 composite lithium cobalt oxide material, the conditions for the molten salt ion exchange treatment are controlled as follows: heating to 180°C-300°C at a heating rate of 1°C / min-10°C / min, and keeping warm for 30min-12h;
[0022] Optionally, the lithium source is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide; the molar ratio of lithium in the lithium source to sodium in the P2 phase precursor is (1-20): 1;
[0023] Optionally, after the molten salt ion exchange treatment, water washing and drying are performed, and the drying temperature is controlled to be 80° C.-150° C., and the drying time is ≥12 h.
[0024] In an optional embodiment, in the process of preparing O2 phase lithium cobalt oxide, the lithium supplementation treatment step includes: mixing water, lithium salt and T2&O2 composite lithium cobalt oxide material, keeping warm at 50°C-95°C for 3h-24h, and controlling the molar ratio of lithium to cobalt in the material after the lithium supplementation treatment to be greater than 0.9;
[0025] Optionally, the lithium salt is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide;
[0026] Optionally, the mass ratio of water, lithium salt and T2&O2 composite lithium cobalt oxide material is 100:(10-30):(2-20);
[0027] Optionally, after the lithium supplementation treatment, water washing and drying are performed, and the drying temperature is controlled to be 80° C.-150° C., and the drying time is ≥12 h.
[0028] In an optional embodiment, the process of forming the boron-containing compound coating layer includes: mixing O2-phase lithium cobalt oxide with a boron-containing coating material, and performing low-temperature solid-phase sintering at 150° C. to 230° C. for 1 h to 12 h;
[0029] Optionally, the boron-containing coating material is selected from at least one of boron oxide, boric acid, lithium metaborate and lithium bis(oxalate)borate;
[0030] Optionally, the mass ratio of the boron-containing coating material to the O2-phase lithium cobalt oxide is (0.2-2.0): 100;
[0031] Optionally, during the low-temperature solid-phase sintering process, the heating rate is controlled to be 1°C / min-10°C / min.
[0032] In a third aspect, the present invention provides a positive electrode plate, comprising the lithium cobalt oxide positive electrode material according to any one of the aforementioned embodiments or the lithium cobalt oxide positive electrode material prepared by any one of the preparation methods according to the aforementioned embodiments.
[0033] In a fourth aspect, the present invention provides a lithium battery comprising the positive electrode sheet of the aforementioned embodiment.
[0034] In a fifth aspect, the present invention provides an electrical device comprising the lithium battery of the aforementioned embodiment.
[0035] The present invention has the following beneficial effects: the lithium cobalt oxide positive electrode material provided by the present invention is a coating layer of a boron compound coated on an O2 phase lithium cobalt oxide main material, and the surface-optimized O2 phase lithium cobalt oxide positive electrode material provided has higher first efficiency, capacity and cycle stability than conventional O3 phase lithium cobalt oxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 The O2 phase lithium cobalt oxide and its characteristic peaks prepared in Example 1; (a) is the XRD spectrum of the O2 phase lithium cobalt oxide; (b) is a local enlarged view of the XRD spectrum of the characteristic peaks of the O2 phase lithium cobalt oxide. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] The development of LiCoO2 cathode materials that are more stable and have higher energy density under high voltage is the current mainstream research direction. O2 phase LiCoO2 has a different spatial arrangement from O3 phase LiCoO2, but can still maintain a stable crystal structure at a higher delithiation state. The CoO6 octahedron in the O2 phase LiCoO2 has a stronger Co-O bond, which enhances the structural stability to resist proton attack and prolongs the cycle life in aqueous electrolytes. In addition, the O2 phase LiCoO2 undergoes a reversible phase change during the cycle process and will not be converted into a thermodynamically stable O3 phase LiCoO2 or spinel phase. In view of this, the inventors prepared a more stable LiCoO2 cathode material with a higher energy density based on the O2 phase LiCoO2.
[0040] However, O2 phase LiCoO2 also has disadvantages, such as low phase transition temperature. It will transform to O3 phase above 230°C and will completely transform to O3 phase above 280°C. The conventional O3 phase LiCoO2 in industry requires the substrate and coating material to be mixed and then subjected to secondary high-temperature calcination to achieve coating (generally >600°C). Therefore, the coating technology used for conventional O3 phase LiCoO2 is difficult to achieve effective coating of O2 phase LiCoO2.
[0041] An embodiment of the present invention provides a lithium cobalt oxide positive electrode material, including a main material and a boron-containing compound coating layer coated on the main material. The boron-containing compound coating layer is used to coat the O2 phase lithium cobalt oxide main material to achieve higher capacity and better cycle stability under high voltage compared to conventional O3 phase lithium cobalt oxide.
[0042] Among them, the general formula of the main material is Li x Na y Co 1-z M z O2, M is a doping element, M is selected from at least one of Mg, Al, W, Ti, La, Zr, Y, Ni and Mn, and M can be any one or more of the above. In the general formula, x, y and z satisfy: 0.9≤x≤1, 0≤y≤0.1, 0<z≤0.1, and 0.9<x / (1-z)<1, such as x can be 0.90, 0.92, 0.95, 0.98, 1.00, etc.; y can be 0.00, 0.03, 0.05, 0.08, 0.10, etc.; z can be 0.01, 0.03, 0.05, 0.08, 0.10, etc.; x / (1-z) represents the lithium-cobalt molar ratio, which is greater than 0.9 and less than 1, such as 0.91, 0.93, 0.95, 0.96, 0.98, 0.99, etc.
[0043] The main XRD peak of lithium cobalt oxide positive electrode material is located at 18.6±0.1°, such as 18.5°, 18.6°, 18.7°, etc., which belongs to O2 phase lithium cobalt oxide.
[0044] In some embodiments, in the lithium cobalt oxide positive electrode material, the mass fraction of the boron-containing compound is 0.1%-1.0%, such as 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, etc.
[0045] The lithium cobalt oxide positive electrode material provided by the embodiment of the present invention has the following advantages over conventional lithium cobalt oxide materials: (1) Compared with O3 phase lithium cobalt oxide, O2 phase lithium cobalt oxide has a more stable structure, and has better first efficiency, capacity and cycle stability at high voltage; (2) Compared with T2 & O2 phase lithium cobalt oxide, O2 phase lithium cobalt oxide has a higher Li / Co ratio and can be used directly at the battery cell end without the need for negative electrode lithium supplementation treatment.
[0046] The present invention also provides a method for preparing a lithium cobalt oxide positive electrode material, comprising the following steps:
[0047] S1. Preparation of P2 phase precursor
[0048] The sodium source and the cobalt source are mixed and sintered, and the molar ratio of sodium to cobalt is adjusted to prepare a P2 phase precursor for later use.
[0049] In some embodiments, the preparation process of the P2 phase precursor includes: mixing a sodium source, a cobalt source and an M source, controlling the heating rate to 1°C / min-10°C / min, heating to 700°C-900°C for high-temperature solid-phase sintering for 8h-30h, and preparing a uniform P2 phase precursor through high-temperature solid-phase sintering and regulating the sintering temperature and time.
[0050] Specifically, the heating rate can be 1°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, etc., the sintering temperature of high-temperature solid-phase sintering can be 700°C, 750°C, 800°C, 850°C, 900°C, etc., and the sintering time can be 8h, 10h, 15h, 20h, 25h, 30h, etc. After the insulation is completed, the furnace is cooled to room temperature.
[0051] The doping element M in the M source is selected from at least one of Mg, Al, W, Ti, La, Zr, Y, Ni and Mn, and the M element can be any one or more of the above. Generally speaking, there is a small amount of aluminum doping in the cobalt source. When the doping element is aluminum, no additional M source is required, that is, a cobalt source containing M element can be used; when the doping element is other elements besides aluminum, additional M source needs to be added.
[0052] In some embodiments, by adjusting the amount of sodium source and cobalt source, the molar ratio of sodium and cobalt is controlled to be (0.6-1.0):1, such as 0.60, 0.70, 0.73, 0.75, 0.80, 0.90, 1.00, etc., preferably (0.70-0.75):1. The sodium-cobalt molar ratio can present a uniform P2 phase within this range.
[0053] Furthermore, the cobalt source is selected from at least one of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide, and the cobalt source can be any one or more of the above. The sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate, and the sodium source can be any one or more of the above.
[0054] S2. Preparation of T2&O2 composite lithium cobalt oxide material
[0055] The P2 phase precursor and the lithium source are mixed and then subjected to molten salt ion exchange treatment, so that lithium basically completely replaces the position of sodium, and only a small amount of sodium remains. Due to the sodium-cobalt ratio in step S1 (such as (0.70-0.75): 1), the lithium-cobalt ratio after ion exchange is approximately equal to the previous sodium-cobalt ratio (also (0.70-0.75): 1), and within this range, a lithium-poor O2 phase (i.e., T2 phase) is presented, and the final product is a composite phase of a large amount of T2 phase and a small amount of O2 phase, i.e., T2&O2 composite lithium cobalt oxide material.
[0056] In some embodiments, during the preparation of T2&O2 composite lithium cobalt oxide material, the conditions of the molten salt ion exchange treatment are controlled as follows: heating to 180°C-300°C at a heating rate of 1°C / min-10°C / min, and keeping warm for 30min-12h. By adjusting the temperature and time of the molten salt ion exchange treatment, lithium can fully occupy the position of sodium and more fully realize the exchange of lithium and sodium.
[0057] Specifically, the heating rate can be 1°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, etc., the treatment temperature of the molten salt ion exchange treatment can be 180°C, 200°C, 230°C, 250°C, 280°C, 300°C, etc., and the insulation time can be 30min, 1h, 5h, 8h, 10h, 12h, etc. After the insulation is completed, the furnace is then cooled to room temperature.
[0058] Furthermore, the lithium source is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide, and the lithium source can be any one or more of the above. The molar ratio of lithium in the lithium source to sodium in the P2 phase precursor is (1-20):1, such as 1:1, 5:1, 10:1, 15:1, 20:1, etc. It is preferable that the lithium is in excess to more fully realize the exchange of lithium and sodium.
[0059] In some embodiments, after the molten salt ion exchange treatment, water washing and drying are performed to remove unreacted lithium on the surface, and the water washing and drying equipment are not limited. The drying temperature is controlled to be 80°C-150°C, and the drying time is ≥12h to fully remove the surface washing water. Specifically, the drying temperature can be 80°C, 100°C, 120°C, 150°C, etc., and the drying time can be 12h, 15h, 20h, 24h, etc.
[0060] S3, O2 phase lithium cobalt oxide
[0061] The T2&O2 composite lithium cobalt oxide material is treated with lithium in a lithium salt solution, and the molar ratio of lithium to cobalt in the material after the lithium treatment is controlled to be greater than 0.9, thereby obtaining O2 phase lithium cobalt oxide. The O2 phase lithium cobalt oxide synthesized in the embodiment of the present invention has a more stable structure than conventional O3 phase lithium cobalt oxide, and has a larger C axis, higher discharge capacity and better cycle stability.
[0062] In some embodiments, in the process of preparing O2-phase lithium cobalt oxide, the lithium supplementation treatment step includes: mixing water, lithium salt and T2&O2 composite lithium cobalt oxide material, keeping warm at 50°C-95°C for 3h-24h, and the mass ratio of water, lithium salt and T2&O2 composite lithium cobalt oxide material is 100:(10-30):(2-20). By adjusting the amount of each raw material and the temperature and time of lithium supplementation treatment, uniform O2-phase lithium cobalt oxide is obtained.
[0063] Specifically, the mass ratio of water, lithium salt and T2&O2 composite lithium cobalt oxide material can be 100:10:2, 100:15:5, 100:20:10, 100:25:15, 100:30:20, etc. The temperature of lithium supplementation treatment can be 50°C, 60°C, 70°C, 80°C, 90°C, 95°C, etc., and the insulation time can be 3h, 5h, 10h, 15h, 20h, 24h, etc.
[0064] Furthermore, the lithium salt is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide, and the lithium salt can be any one or more of the above.
[0065] Furthermore, after the lithium supplementation treatment, water washing and drying are performed to remove the unreacted raw materials on the surface, and the washing water is removed by drying. The water washing and drying equipment are not limited. The drying temperature is controlled to be 80°C-150°C, such as 80°C, 100°C, 120°C, 150°C, etc.; the drying time is ≥12h, such as 12h, 15h, 20h, 24h, etc.
[0066] S4. Forming a boron compound coating layer
[0067] The O2 phase lithium cobalt oxide is mixed with a boron-containing coating material and solid-phase sintered to form a coating layer containing a boron compound on the surface.
[0068] In some embodiments, O2 phase lithium cobalt oxide is mixed with a boron-containing coating material, the heating rate is controlled to be 1°C / min-10°C / min, and the temperature is raised to 150°C-230°C for low-temperature solid-phase sintering for 1h-12h. The sintering temperature and time of the low-temperature solid-phase sintering are adjusted to form a uniform boron compound coating layer. The coating method provided in the embodiment of the present invention only requires low-temperature secondary sintering to achieve, which maintains the O2 phase structure of the bulk phase, and the boron-containing compound selected for coating generates a stable interface on the surface. Under the premise of not affecting the diffusion of lithium ions, the interface side reactions are suppressed, the structure is stabilized, and the cycle stability of the material is improved. Compared with the conventional O3 phase lithium cobalt oxide coating technology, the coating method provided in the embodiment of the present invention does not require high-temperature sintering and maintains the O2 phase structure of the bulk phase.
[0069] Specifically, the heating rate can be 1°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, etc., the temperature of low-temperature solid-phase sintering can be 150°C, 180°C, 200°C, 210°C, 230°C, etc., and the holding time can be 1h, 5h, 8h, 10h, 12h, etc. After the holding is completed, the furnace is cooled to room temperature.
[0070] In some embodiments, the boron-containing coating material is selected from at least one of boron oxide, boric acid, lithium metaborate and lithium bis(oxalate) borate. The boron-containing coating material can be any one or more of the above. The preferred boron-containing compound for coating is acidic, which has a positive effect on eliminating residual alkali on the surface of the material. The mass ratio of the boron-containing coating material to the O2-phase lithium cobalt oxide is (0.2-2.0):100, such as 0.2:100, 0.5:100, 0.8:100, 1.0:100, 1.2:100, 1.5:100, 1.8:100, 2.0:100, etc.
[0071] It should be noted that the synthesis method and coating method provided in the embodiments of the present invention are simple and easy to implement, and the coating raw materials are readily available, which are suitable for industrial large-scale production.
[0072] The embodiment of the present invention provides a positive electrode sheet, including the lithium cobalt oxide positive electrode material provided in the embodiment of the present invention, using the lithium cobalt oxide positive electrode material as a positive electrode active material to form a positive electrode active coating on a positive electrode current collector. Other components of the positive electrode active coating are not limited and can refer to the prior art.
[0073] An embodiment of the present invention further provides a lithium battery, including the above-mentioned positive electrode plate, and may also include a negative electrode plate, an electrolyte, etc., to form a complete lithium battery structure.
[0074] An embodiment of the present invention further provides an electrical device, including the above-mentioned lithium battery, which is powered by the lithium battery. The specific form of the electrical device is not limited, such as an electric vehicle, an electronic device, etc.
[0075] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0076] Example 1
[0077] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material, and the specific steps are as follows:
[0078] (1) Na2CO3 and Co3O4 were uniformly mixed at a Na / Co molar ratio of 0.74 and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor;
[0079] (2) The P2Na precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein nLiNO3:nLiCl is 71:29, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping warm for 1h, cooling with the furnace, washing and drying (100°C, 15h, the same below), to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0080] (3) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, the ratio of mT2&O2:mlithium hydroxide:mdeionized water is 1:2.33:20, the solution is placed in a sealed container, and is placed in a 95°C oven for 24 hours, washed and dried (100°C, 15 hours, the same below), to obtain O2 phase lithium cobalt oxide;
[0081] (4) The O2 phase lithium cobalt oxide and lithium bis(oxalate borate) are uniformly mixed and then sintered at low temperature. The amount of lithium bis(oxalate borate) added is 0.5wt% (i.e., the mass ratio of lithium bis(oxalate borate) to O2 phase lithium cobalt oxide is 0.5:100). The sintering process is to heat the mixture to 180°C at 1°C / min, keep the mixture at that temperature for 2h, cool the mixture with the furnace, grind and sieve the mixture, and obtain the O2 phase lithium cobalt oxide coated with a surface boron-containing compound.
[0082] Example 2
[0083] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material, and the specific steps are as follows:
[0084] (1) Na2CO3 and Co3O4 were uniformly mixed at a Na / Co molar ratio of 0.74 and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor;
[0085] (2) The P2Na precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein nLiNO3:nLiCl is 71:29, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0086] (3) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, the ratio of mT2&O2:mlithium hydroxide:mdeionized water is 1:2.33:20, the solution is placed in a sealed container, and is placed in an oven at 95°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide;
[0087] (4) After uniformly mixing O2-phase lithium cobalt oxide and boric acid, the mixture is sintered at a low temperature. The amount of boric acid added is 0.5 wt %. The sintering process is to increase the temperature to 180° C. at 1° C. / min, keep the temperature for 2 h, cool with the furnace, grind and sieve to obtain O2-phase lithium cobalt oxide coated with a surface boron-containing compound.
[0088] Example 3
[0089] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material, and the specific steps are as follows:
[0090] (1) Na2CO3 and Co3O4 were uniformly mixed at a Na / Co molar ratio of 0.74 and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor;
[0091] (2) The P2Na precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein nLiNO3:nLiCl is 71:29, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0092] (3) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, the ratio of mT2&O2:mlithium hydroxide:mdeionized water is 1:2.33:20, the solution is placed in a sealed container, and is placed in an oven at 95°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide;
[0093] (4) The O2 phase lithium cobalt oxide and lithium metaborate are uniformly mixed and then sintered at low temperature. The amount of lithium metaborate added is 0.5 wt %. The sintering process is to increase the temperature to 180° C. at 1° C. / min, keep the temperature for 2 h, cool with the furnace, grind and sieve to obtain the O2 phase lithium cobalt oxide coated with a surface boron-containing compound.
[0094] Example 4
[0095] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material, and the specific steps are as follows:
[0096] (1) Na2CO3 and Co3O4 were uniformly mixed at a Na / Co molar ratio of 0.74 and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor;
[0097] (2) The P2Na precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein nLiNO3:nLiCl is 71:29, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0098] (3) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, the ratio of mT2&O2:mlithium hydroxide:mdeionized water is 1:2.33:20, the solution is placed in a sealed container, and is placed in an oven at 95°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide;
[0099] (4) After uniformly mixing O2-phase lithium cobalt oxide and boron oxide, sintering is performed at low temperature. The amount of boron oxide added is 0.5 wt %. The sintering process is to increase the temperature to 180° C. at 1° C. / min, keep the temperature for 2 h, cool with the furnace, grind and sieve to obtain O2-phase lithium cobalt oxide coated with a surface boron-containing compound.
[0100] Example 5
[0101] The only difference from Example 1 is that the sintering temperature in step (4) is 230°C.
[0102] Example 6
[0103] The only difference from Example 1 is that the amount of lithium bis(oxalate borate) added in step (4) is 0.8 wt %.
[0104] Comparative Example 1
[0105] (1) Li2CO3 and Co3O4 were uniformly mixed at a Li / Co molar ratio of 1.05 and then sintered at high temperature. The sintering process was as follows: heating to 750°C at 4°C / min, keeping the temperature for 3.5 h, then heating to 1000°C at 2°C / min, keeping the temperature for 6.5 h, cooling in the furnace, grinding and sieving to obtain conventional O3 phase lithium cobalt oxide.
[0106] Comparative Example 2
[0107] (1) Na2CO3 and Co3O4 were uniformly mixed at a Na / Co molar ratio of 0.74 and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor;
[0108] (2) The P2Na precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein nLiNO3:nLiCl is 71:29, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0109] (3) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, with the ratio of mT2&O2:mlithium hydroxide:mdeionized water being 1:2.33:20. The solution is placed in a sealed container, and allowed to stand in an oven at 95°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide.
[0110] It should be noted that the difference between Comparative Example 2 and Example 1 is only that step (4) is not performed.
[0111] Comparative Example 3
[0112] (1) Na2CO3 and Co3O4 were uniformly mixed at a Na / Co molar ratio of 0.74 and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor;
[0113] (2) The P2Na precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein nLiNO3:nLiCl is 71:29, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0114] (3) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, the ratio of mT2&O2:mlithium hydroxide:mdeionized water is 1:2.33:20, the solution is placed in a sealed container, and is placed in an oven at 95°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide;
[0115] (4) The O2 phase lithium cobalt oxide and lithium bis(oxalate borate) are uniformly mixed and then sintered at low temperature. The amount of lithium bis(oxalate borate) added is 0.5wt%. The sintering process is to increase the temperature to 250°C at 1°C / min, keep the temperature for 2h, cool with the furnace, grind and sieve to obtain O2&O3 phase lithium cobalt oxide with a surface boron-containing compound coating.
[0116] It should be noted that the difference between Comparative Example 3 and Example 1 is only that the sintering temperature in step (4) is different.
[0117] Comparative Example 4
[0118] The only difference from Example 1 is that the sintering temperature in step (4) is 120°C.
[0119] Test Example 1
[0120] The XRD pattern of the O2-phase lithium cobalt oxide coated with the surface boron-containing compound prepared in step (4) of test example 1 is as follows: Figure 1 shown.
[0121] Figure 1 It can be seen that the XRD peak corresponds to the main peak of O2 phase lithium cobalt oxide of PDF#36-1004, and there are no other impurity peaks, indicating that the product is pure O2 phase lithium cobalt oxide, and the introduction of surface boron-containing compounds has no obvious effect on the physical phase.
[0122] Test Example 2
[0123] The boron content in Examples 1-4 was tested by inductively coupled plasma spectrometer, and the test results are shown in Table 1.
[0124] The positive electrode material prepared in the embodiment and the comparative example is used as the positive electrode active material, Super P is a conductive agent, polyvinylidene fluoride (PVDF) is a binder, and the mass ratio of the above three is 90:5:5. An appropriate amount of N-methylpyrrolidone (NMP) is added to control the solid content of the slurry to 40%, and the slurry is evenly mixed and applied to the aluminum foil current collector. After vacuum drying, it is taken out and hot pressed, and cut into a positive electrode sheet with a diameter of 12mm and a thickness of about 60μm. The button lithium-ion battery is assembled from the above-mentioned positive electrode sheet, lithium sheet negative electrode, diaphragm between the positive and negative electrodes, and electrolyte. The assembled battery is placed in a 45℃ high and low temperature box, and a constant current charge and discharge cycle test is performed on the Xinwei battery test channel. The test conditions are: charge and discharge cut-off voltage 3.0-4.65V (vs Li+ / Li), the first cycle charge and discharge rate is 0.1C, the second cycle charge and discharge rate is 0.2C, and the cycle is 50 cycles. The test results are shown in Table 1.
[0125] Table 1 Comparison of boron content and electrochemical performance of samples of examples and comparative examples
[0126]
[0127]
[0128] It can be seen from Table 1 that the lithium cobalt oxide positive electrode material prepared in the embodiment of the present invention has a higher first efficiency, a higher initial capacity and a higher capacity retention rate than that of the comparative example.
[0129] Examples 1-4 compare different boron contents, and it can be seen that the coating amount in Example 1 is more conducive to improving the electrochemical performance of the material.
[0130] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium cobalt oxide positive electrode material, characterized in that: It comprises a main body material and a boron compound coating layer coated on the main body material; Wherein, the general formula of the main material is Li x Na y Co 1-z M z O2, M is at least one selected from Mg, Al, W, Ti, La, Zr, Y, Ni and Mn, 0.9≤x≤1, 0≤y≤0.1, 0<z≤0.1, and 0.9<x / (1-z)<1; The XRD main peak of the lithium cobalt oxide positive electrode material is located at 18.6±0.1°.
2. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that: In the lithium cobalt oxide positive electrode material, the mass fraction of the boron-containing compound is 0.1%-1.0%.
3. A method for preparing the lithium cobalt oxide positive electrode material according to claim 1 or 2, characterized in that: include: Mixing the sodium source and the cobalt source and sintering them to obtain a P2 phase precursor; The P2 phase precursor and the lithium source are mixed and then subjected to molten salt ion exchange treatment to obtain a T2&O2 composite lithium cobalt oxide material; The T2&O2 composite lithium cobalt oxide material is subjected to lithium supplementation treatment in a lithium salt solution to obtain O2 phase lithium cobalt oxide; A boron compound coating layer is formed on the O2 phase lithium cobalt oxide.
4. The preparation method according to claim 3, characterized in that: The preparation process of the P2 phase precursor comprises: mixing a sodium source, a cobalt source and an M source, and performing high temperature solid phase sintering at 700° C. to 900° C. for 8 h to 30 h; M is selected from at least one of Mg, Al, W, Ti, La, Zr, Y, Ni and Mn; Optionally, the molar ratio of sodium to cobalt is controlled to be (0.6-1.0):1; Optionally, the cobalt source is selected from at least one of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide; Optionally, the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate; Optionally, during the high-temperature solid-phase sintering process, the heating rate is controlled to be 1°C / min-10°C / min.
5. The preparation method according to claim 3, characterized in that: In the process of preparing the T2&O2 composite lithium cobalt oxide material, the conditions of the molten salt ion exchange treatment are controlled as follows: heating to 180°C-300°C at a heating rate of 1°C / min-10°C / min, and keeping warm for 30min-12h; Optionally, the lithium source is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide; the molar ratio of lithium in the lithium source to sodium in the P2 phase precursor is (1-20): 1; Optionally, after the molten salt ion exchange treatment, water washing and drying are performed, and the drying temperature is controlled to be 80° C.-150° C., and the drying time is ≥12 h.
6. The preparation method according to claim 3, characterized in that: In the process of preparing the O2 phase lithium cobalt oxide, the lithium supplementation treatment step includes: mixing water, lithium salt and the T2&O2 composite lithium cobalt oxide material, keeping the temperature at 50°C-95°C for 3h-24h, and controlling the molar ratio of lithium to cobalt in the material after the lithium supplementation treatment to be greater than 0.9; Optionally, the lithium salt is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide; Optionally, the mass ratio of water, the lithium salt and the T2&O2 composite lithium cobalt oxide material is 100:(10-30):(2-20); Optionally, after the lithium supplementation treatment, water washing and drying are performed, and the drying temperature is controlled to be 80° C.-150° C., and the drying time is ≥12 h.
7. The preparation method according to claim 3, characterized in that: The process of forming the boron-containing compound coating layer comprises: mixing the O2-phase lithium cobalt oxide with the boron-containing coating material, and performing low-temperature solid-phase sintering at 150° C. to 230° C. for 1 h to 12 h; Optionally, the boron-containing coating material is selected from at least one of boron oxide, boric acid, lithium metaborate and lithium bis(oxalate)borate; Optionally, the mass ratio of the boron-containing coating material to the O2-phase lithium cobalt oxide is (0.2-2.0): 100; Optionally, during the low-temperature solid-phase sintering process, the heating rate is controlled to be 1°C / min-10°C / min.
8. A positive electrode sheet, characterized in that: The invention comprises the lithium cobalt oxide positive electrode material according to any one of claims 1 to 2 or the lithium cobalt oxide positive electrode material prepared by the preparation method according to any one of claims 3 to 7.
9. A lithium battery, characterized in that: Including the positive electrode sheet as described in claim 8.
10. An electrical device, characterized in that: Including the lithium battery as described in claim 9.
Citation Information
Patent Citations
Cathode material for boracic lithium ion battery and preparation method thereof
CN105244492A
Modified positive electrode material and preparation method thereof, positive electrode sheet and lithium ion battery
CN113675383A
Coated modified lithium cobalt oxide material and preparation method thereof, positive plate and lithium ion battery
CN114551826A
Method for modifying lithium cobalt oxide and nickel-cobalt-manganese ternary material by boron-containing compound and high-voltage lithium cobalt oxide and nickel-cobalt-manganese ternary material
CN115528219A
Lithium cobalt oxide positive electrode material, preparation method thereof and secondary battery
CN118538910A
Cited By
Layered lithium battery positive electrode material as well as preparation method and application thereof
CN120784354A
O2-phase lithium cobalt oxide positive electrode material and preparation method and application thereof
CN121134846A
O2-phase lithium cobalt oxide positive electrode material and preparation method thereof, secondary battery and electric device
CN121269822A